The influence of negative educational experiences on health behaviors among gender nonconforming American Indian/Alaska Native people - Martin, Chicora, author; Banning, James, advisor; Rankin, Sue, committee member; Carlson, Laurie, committee member; Vernon, Irene, committee member (Colorado State University. Libraries, 2013)
Utilizing data from the National Transgender Discrimination Survey (NTDS) Public Use dataset which reports data collected in the 2009 National Transgender Discrimination Survey (NTDS), completed by The National Center for Transgender Equality and the National Gay and Lesbian Task Force, the purpose of this study is to provide more insight into transgender and gender nonconforming Indigenous people's experiences in education and the impact on health behaviors. With 329 responses from those participants identifying as American Indian/ Alaska Native, the quantitative analysis methods of bivariate correlations and logistic regression were used to analyze the impact of harassment and policy barriers in higher education settings on substance use and suicidality for gender nonconforming Indigenous people. Both substance use and suicidality are impacted by the experiences of harassment and barriers in the higher education setting. The impact of these experiences on suicidality is especially concerning, as the rate of over 53% for gender nonconforming Indigenous students is higher than any other group within this sample. This analysis offers some insight into these experiences of this population and how important interventions in the higher education setting--related to both reducing incidents of harassment and addressing policy and access barriers--may be to the success of gender nonconforming Indigenous students in college.
Keywords: American Indian; gender nonconforming; higher education; substance use; suicide; transgender